Bipolar Disorder after Stroke in an Elderly Patient. (4th June 2014) - Melo, Raquel Calvão de; Lopes, Rui; Alves, José Carlos
Abstract : The onset of bipolar disorder (BD) secondary to a stroke event is a rare clinical entity. Although it may be related to specific regions of the brain, several other factors have been linked to its expression such as subcortical atrophy or chronic vascular burden. While precise locations and cerebral circuits involved in the bipolarity expression after stroke still need to be determined, their investigation represents an opportunity to study brain function and BD etiopathogenesis. We present a BD secondary to multiple subcortical biparietal lacunar infarctions, a lacunar infarction in left putamen and an ischemic lesion at the cerebral trunk evolving the right median portion, in a 65-year-old male patient who experienced manic, hypomanic, and depressive episodes, after 6, 10, and 16 months, respectively, of the cerebrovascular events.